Health Implications of Pickleball - Kumar, Sneha (Journal of Educational Research and Policies, 2025)
Pickleball is a sport that is considered a combination of table tennis, badminton and tennis. Pickleball is played with a racket similar to a table tennis racket but larger than a table tennis racket, the Pickleball ball, similar in size to a tennis ball, is made of hollow plastic and has holes. When playing this sport, players will play on a court that is similar in size to a badminton court, but the net will be placed close to the ground like tennis, while the court lines are divided into squares like badminton. Pickleball was born in the United States in 1965, Pickleball is known as one of the fastest growing sports in the world. In the past 5 years, this sport has begun to appear in Vietnam and has quickly attracted many people to participate in practice. Pickleball attracts individuals of all ages, not just young people. Playing pickleball regularly can help improve flexibility, endurance, increase muscle strength, stabilize cardiovascular health and control weight. In addition, this sport is quickly becoming a trend thanks to the connection with others with similar interests, promoting community participation, reducing stress and improving mental health.